In-situ incubation of a coral patch for community-scale assessment of metabolic and chemical processes on a reef slope - van Heuven, Steven M.A.C.; Webb, Alice E.; de Bakker, Didier M.; Meesters, Erik; van Duyl, Fleur C.; Reichart, Gert-Jan; de Nooijer, Lennart J. (PeerJ, 2018)
Anthropogenic pressures threaten the health of coral reefs globally. Some of these pressures directly affect coral functioning, while others are indirect, for example by promoting the capacity of bioeroders to dissolve coral aragonite. To assess the coral reef status, it is necessary to validate community-scale measurements of metabolic and geochemical processes in the field, by determining fluxes from enclosed coral reef patches. Here, we investigate diurnal trends of carbonate chemistry, dissolved organic carbon, oxygen, and nutrients on a 20 m deep coral reef patch offshore from the island of Saba, Dutch Caribbean by means of tent incubations. The obtained trends are related to benthic carbon fluxes by quantifying net community calcification (NCC) and net community production (NCP). The relatively strong currents and swell-induced near-bottom surge at this location caused minor seawater exchange between the incubated reef and ambient water. Employing a compensating interpretive model, the exchange is used to our advantage as it maintains reasonably ventilated conditions, which conceivably prevents metabolic arrest during incubation periods of multiple hours. No diurnal trends in carbonate chemistry were detected and all net diurnal rates of production were strongly skewed towards respiration suggesting net heterotrophy in all incubations. The NCC inferred from our incubations ranges from −0.2 to 1.4 mmol CaCO3 m−2 h−1 (−0.2 to 1.2 kg CaCO3 m−2 year−1) and NCP varies from −9 to −21.7 mmol m−2 h−1 (net respiration). When comparing to the consensus-based ReefBudget approach, the estimated NCC rate for the incubated full planar area (0.36 kg CaCO3 m−2 year−1) was lower, but still within range of the different NCC inferred from our incubations. Field trials indicate that the tent-based incubation as presented here, coupled with an appropriate interpretive model, is an effective tool to investigate, in situ, the state of coral reef patches even when located in a relatively hydrodynamic environment.
Keywords: Coral reef; Incubation; Alkalinity anomaly